Molecular doping and trap filling in organic semiconductor host-guest systems - Zuo, Guangzheng; Li, Zhaojun; Andersson, Olof; Abdalla, Hassan; Wang, Ergang; Kemerink, Martijn (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
We investigate conductivity and mobility of different hosts mixed with different electron-withdrawing guests in concentrations ranging from ultralow to high. The effect of the guest material on the mobility and conductivity of the host material varies systematically with the guests’ LUMO energy relative to the host HOMO, in quantitative agreement with a recently developed model. For guests with a LUMO within ∼0.5 eV of the host HOMO the dominant process governing transport is the competition between the formation of a deep tail in the host DOS and state filling. In other cases, the interaction with the host is dominated by any polar side groups on the guest and changes in the host morphology. For relatively amorphous hosts the latter interaction can lead to a suppression of deep traps, causing a surprising mobility increase by 1-2 orders of magnitude. In order to analyze our data, we developed a simple method to diagnose both the presence and the filling of traps.